2017
DOI: 10.1007/s00784-017-2102-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal exposure to tobacco, presence of TGFA gene, and the occurrence of oral clefts. A case control study

Abstract: The study has brought into forth the role of passive smoking in the development of oral clefts thereby warranting an effective public health policy to tackle the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Paternal smoking was evaluated in a subset of the current data from Vietnam, the Philippines, Morocco, and Honduras (n = 626 father/child duos) and no association with cleft was found [ 32 ]. Studies in Norway [ 33 ], India [ 34 ], and China [ 35 ] have found that exposure to ETS, defined as an exposure to passive tobacco smoke during the first trimester at home or work, is associated with an increased risk of cleft (OR = 1.6, 95% CI = 1.0-2.5; OR = 2.0, 95% CI = 1.2-3.4; OR = 2.46, 95% CI = 0.99-6.08, respectively), however a case-control study based in a large American birth defect registry found no effect [ 31 ]. Our study did not see an effect of either paternal smoking or ETS, where ETS is defined as maternal report of passive smoke exposure in the home during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Paternal smoking was evaluated in a subset of the current data from Vietnam, the Philippines, Morocco, and Honduras (n = 626 father/child duos) and no association with cleft was found [ 32 ]. Studies in Norway [ 33 ], India [ 34 ], and China [ 35 ] have found that exposure to ETS, defined as an exposure to passive tobacco smoke during the first trimester at home or work, is associated with an increased risk of cleft (OR = 1.6, 95% CI = 1.0-2.5; OR = 2.0, 95% CI = 1.2-3.4; OR = 2.46, 95% CI = 0.99-6.08, respectively), however a case-control study based in a large American birth defect registry found no effect [ 31 ]. Our study did not see an effect of either paternal smoking or ETS, where ETS is defined as maternal report of passive smoke exposure in the home during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in the MEE cells during palatal fusion (Ebadifar et al, 2016; Mitchell, 1997; Vieira & Orioli, 2001), and is known to regulate extracellular matrix synthesis and mesenchymal migration in palatal cultures (Ebadifar et al, 2016; Holder, Vintiner, Farren, Malcolm, & Winter, 1992; Machida et al, 1999; Qian, Feingold, Stoll, & May, 1993; Shiang et al, 1993). Variants effecting TGFA ‐smoking GxE have been observed in several populations (Ebadifar et al, 2016; Hwang et al, 1995; Junaid, Narayanan, Jayanthi, Kumar, & Selvamary, 2018; Maestri et al, 1997; G. M. Shaw et al, 1996; Sull et al, 2009). TGFB3 encodes a ligand that regulates TGF‐β signaling which is critical for lip and palatal development (Reynolds et al, 2020; in this issue).…”
Section: Behavioral Risk Factors For Ofcsmentioning
confidence: 99%
“…Researchers found a strong association between orofacial clefts and family history (Figueiredo et al, 2015) and the literature suggests that family history is a strong component to be considered in predicting the potential risk of new cases of orofacial clefts in the family. Moreover, this factor may be associated with an increased risk of occurrence of cleft in the family (Junaid et al, 2018; Leite & Koifman, 2009; Li et al, 2016; Lin et al, 2014; Mbuyi‐Musanzayi et al, 2018). Studies have shown that the risk of occurrence of clefts in families of individuals already affected can be 4.6–8.2 times greater than what occurs in the general population (Acuña‐González et al, 2011; Salihu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this factor may be associated with an increased risk of occurrence of cleft in the family (Junaid et al, 2018;Leite & Koifman, 2009;Li et al, 2016;Lin et al, 2014;Mbuyi-Musanzayi et al, 2018).…”
mentioning
confidence: 99%